EFFECTS OF FEED REDUCTION ON GROWTH PERFORMANCE, WATER QUALITY, AND HEMATOLOGY STATUS OF AFRICAN CATFISH, Clarias gariepinus REARED IN BIOFLOC POND SYSTEM - Azam Bachur Zaidy; Yuke Eliyani; Toni Ruchimat (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2022)
Biofloc technique is a method of fish culture using minimal water exchange and microbial aggregates formed within the culture media as fish supplementary feed. Biofloc as a protein source is currently not being considered part of the feeding dosage in catfish culture. This present work aimed to determine the effects of commercial feed reduction on growth performance, water quality, and hematology of catfish cultured in biofloc ponds. Fish with an average body weight of 7.53 ± 0.47 g were stocked in nine ponds with a stocking density of 100 fish/pond and reared for nine weeks. The experiment was arranged in a completely randomized design, with the following treatments: full feed + non-biofloc (C100) as control; 10% less feed + biofloc (B90); 20% less feed + biofloc (B80). As such, the total feed doses given daily per each treatment fish biomass were: 5% for C100, 4.5% for B90, and 4.0% for B80. Each treatment was arranged in triplicates. The results showed that all water quality parameters (dissolved oxygen, pH, TAN, and nitrite) and biofloc concentrations did not differ significantly among the treatments (P>0.05). Specific growth rate, survival rate, weight gain, and feed conversion ratio of the fish were also not significantly different (P>0.05). The weight gain of biofloc-treated fish in B90 and B80 reached 2.71% and 12.65%, respectively; which were higher than the control treatment during the treatment period. The feed conversion ratios of B90 and B80 were 14.39% and 7.58%, respectively; lower than the control treatment. The biofloc treatment did not adversely alter the fish’s blood cell profiles. This study revealed that feed reduction did not affect water quality in the ponds and blood cell profiles of the fish. Moreover, fish in the biofloc-treated ponds had higher weight gain and lower food conversion ratios compared to fish cultured in the non-treated biofloc ponds. This study suggests that using the biofloc system in catfish rearing can reduce the use of feed up to 10%-20% with similar biomass yield compared to the non-biofloc system.